AB0760 Real-World Validation of the Minimal Disease Activity Index in Psoriatic Arthritis: an Analysis from the Prospective, Observational Registry, Biotrac. (10th June 2014) - Rahman, P.; Shaikh, S.; Starr, M.; Bensen, W.; Choquette, D.; Olszynski, W.; Sheriff, M.; Zummer, M.; Rampakakis, E.; Sampalis, J.S.; Lehman, A.; Otawa, S.; et al.
Abstract : Background: A definition of minimal disease activity (MDA) in PsA was derived from the opinion of 60 PsA experts including fulfillment of ≥5 of the 7 following criteria: tender joint count (TJC) ≤1, swollen joint count (SJC) ≤1, PASI ≤1 or body surface area ≤3%, pain (VAS) ≤15, patient global disease activity (PtGA) (VAS) ≤20, HAQ ≤0.5, and tender entheseal points ≤1 (1). Objectives: To describe the rate of MDA achievement over time and to assess the association between MDA achievement and DAS28 remission in PsA patients treated with anti-TNF in a routine clinical practice setting. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for rheumatoid arthritis (RA), ankylosing spondylitis (AS), or PsA with infliximab or golimumab as first biologics or after having been treated with a biologic for <6 months. Data from PsA patients treated with infliximab (enrolled in 2005-2013) or golimumab (enrolled in 2010-2013) who had available MDA information at baseline, 6 months, and/or 12 months were included. Improvement in patient parameters over time was assessed for statistical significance with the paired-samples t-test. Agreement between MDA and remission as defined by the DAS28 (<2.6) criteria was assessed with the sensitivity, specificity, as well as the positive (PPV) and negative (NPV) predictive value. Results: A total of 123 PsA patients with mean (SD) age of 50.5 (10.5) yrs and mean (SD) duration since diagnosis of 6.1 (7.3) yrs were included in this analysis, providing information from 340 assessments. At the time of enrollment in the registry, mean (SD) patient parameters were: DAS28 =4.2 (1.5), PASI =2.7 (4.8), SJC28 =4.1 (3.5), TJC28 =6.1 (5.6), morning stiffness =45.4 (43.0) min, health assessment questionnaire (HAQ-DI) =1.09 (0.65), physician global assessment of disease activity (MDGA) =5.3 (2.1), patient global assessment of disease activity (PtGA) =49.3 (27.3) mm, and pain =46.5 (25.2) mm. By 6 mos of treatment, statistically significant (P<0.05) improvements were observed in all clinical and patient outcome parameters studied, which were sustained or further enhanced over 12 months of treatment. The proportion of patients with MDA significantly increased from 12.3% at baseline to 45.0% after 6 months of treatment (P<0.001), and 41.9% at 12 mos (P=0.021). Similarly, DAS28 remission was observed in 15.9%, 47.8% and 45.1% of patients at baseline, 6 mos, and 12 mos, respectively. Using DAS28 as reference standard, sensitivity was 69.8%, specificity 93.0%, NPV 88.2%, and PPV 80.4%. Conclusions: MDA has high discriminatory power for remission as defined by the DAS28 criteria, while being more rigorous than DAS28. Furthermore, treatment with anti-TNF is effective in inducing MDA in 45% of patients as early as 6 mos from treatment initiation. References: Coates LC, Cook R, Lee KA, Chandran V, Gladman DD. Arthritis Care Res (Hoboken). 2010 Jul;62(7):970-6. Disclosure of Interest: P. Rahman: None declared, S. Shaikh: None declared, M. Starr: None declared, W. Bensen: None declared, D. Choquette: None declared, W. Olszynski: None declared, M. Sheriff: None declared, M. Zummer: None declared, E. Rampakakis: None declared, J. Sampalis: None declared, A. Lehman Employee of: Janssen, S. Otawa Employee of: Janssen, F. Nantel Employee of: Janssen, V. Letourneau Employee of: Janssen, M. Shawi Employee of: Janssen DOI: 10.1136/annrheumdis-2014-eular.2382